2011
DOI: 10.1179/sic.2011.56.2.125
|View full text |Cite
|
Sign up to set email alerts
|

On the Early History of Museum Environment Control - Nationalmuseum and Gripsholm Castle in Sweden, c.1866-1932

Abstract: NatiONalMusEuM aNd GripsHOlM CastlE iN swEdEN, c. Mattias Legnér

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The provision of a reasonable climate for both objects and visitors had become a matter of concern to museums during the nineteenth century (Legnér, 2011;Eibl & Burmester, 2013, Luciani et al, 2013. In the early 1890s, the Alte Pinakothek, Munich, Germany, began the installation of a low-pressure steam heating system that not only heated the galleries, but also provided some humidification.…”
Section: Buildings Their Environments and Collectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The provision of a reasonable climate for both objects and visitors had become a matter of concern to museums during the nineteenth century (Legnér, 2011;Eibl & Burmester, 2013, Luciani et al, 2013. In the early 1890s, the Alte Pinakothek, Munich, Germany, began the installation of a low-pressure steam heating system that not only heated the galleries, but also provided some humidification.…”
Section: Buildings Their Environments and Collectionsmentioning
confidence: 99%
“…Here, monitoring the effects of variations in RH on objects in the collection indicated that the value most suitable for paintings and most other works of art was 55-60%, regardless of temperature and the time of year, although this value was too high for armour, on which corrosion occurred unless it was coated with a wax finish; these conditions were also unsuitable for early Egyptian art works (McCabe, 1931). By the 1930s, many collections, particularly in the USA, had some degree of temperature and/or RH control, and museums in Europe were also investigating the possibilities of air conditioning or other forms of environmental control (Keeley & Rawlins, 1951;Legnér, 2011;Eibl & Burmester, 2013).…”
Section: Buildings Their Environments and Collectionsmentioning
confidence: 99%
“…The major appeal of these systems was that they allowed to produce a uniform indoor climate or even a different indoor climate from the outdoor one. However, the set-points to which many of the museums regulated their climate at the time were not based on concrete evidence that they really safeguarded the collections [3]. It is obvious that the awareness of this limitation led to the increase of studies focussed on the collections' needs on the coming years.…”
Section: Introductionmentioning
confidence: 99%
“…The control of these parameters has been studied in churches [35] and museums [69]. Microclimatic monitoring studies have also been conducted in open archaeological sites [10,11].…”
Section: Introductionmentioning
confidence: 99%